SGLT2 inhibitors suppress epithelial–mesenchymal transition in podocytes under diabetic conditions via downregulating the IGF1R/PI3K pathway - Guo, Ruixue; Wang, Peipei; Zheng, Xuejun; Cui, Wen; Shang, Jin; Zhao, Zhanzheng (Frontiers in Pharmacology, 2022)
Loss of podocyte is a characteristic pathologic change of diabetic nephropathy (DN) which is associated with increased proteinuria. Many studies have shown that novel inhibitors of sodium-glucose cotransporter 2 (SGLT2-is), such as dapagliflozin, exert nephroprotective effect on delaying DN progression. However, the mechanisms underlying SGLT2-associated podocyte injury are still not fully elucidated. Here, we generated streptozotocin-induced DN models and treated them with dapagliflozin to explore the possible mechanisms underlying SGLT2 regulation. Compared with mice with DN, dapagliflozin-treated mice exhibited remission of pathological lesions, including glomerular sclerosis, thickening of the glomerular basement membrane (GBM), podocyte injury in the glomeruli, and decreased nephrotoxin levels accompanied by decreased SGLT2 expression. The mRNA expression profiles of these treated mice revealed the significance of the insulin-like growth factor-1 receptor (IGF1R)/PI3K regulatory axis in glomerular injury. KEGG analysis confirmed that the phosphatidylinositol signaling system and insulin signaling pathway were enriched. Western blots showed that SGLT2-is inhibited the increase of mesenchymal marker (α-SMA, SNAI-1and ZEB2) and the loss of podocyte marker (Nephrin and E-cad). Additionally, SGLT2, IGF1R, phosphorylated PI3K, α-SMA, SNAI-1and ZEB2 protein levels were increased in high glucose -stimulated human podocytes (HPC) and significantly decreased in dapagliflozin-treated (50 nM and 100 nM) or OSI-906-treated (inhibitor of IGF1R, 60 nM) groups. However, the use of both inhibitors did not enhance this protective effect. Next, we analyzed urine and plasma samples from a cohort consisting of 13 healthy people, and 19 DN patients who were administrated SGLT2 inhibitors (n=9) or not (n=10). ELISA results showed increased circulating levels of IGF1 in SGLT2-is-treated DN patients compared with DN patients. Taken together, our study reported the key role of SGLT2/IGF1R/PI3K signaling in regulating podocyte epithelial-mesenchymal transition (EMT). Modulating the IGF1R expression may be a novel approach for DN therapy.